2014
DOI: 10.1016/j.eats.2013.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Creation of an Anatomic Femoral Tunnel With Minimal Damage to the Remnant Bundle in Remnant-Preserving Anterior Cruciate Ligament Reconstruction Using an Outside-In Technique

Abstract: We established a method for creation of an anatomic femoral tunnel with minimal damage to the remnant bundle in remnant-preserving anterior cruciate ligament (ACL) reconstruction. The goals of this surgical technique were to preserve the remnant bundle as much as possible, especially at the femoral insertion, and to make the tunnel at the anatomic position. The critical points are that the posterior side of the femoral footprint of the ACL is observed through the posterolateral portal using a 70 arthroscope an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 27 publications
1
28
0
Order By: Relevance
“…Under visualization through the PL portal using a 70° arthroscope and through the TS portal, the anatomic femoral tunnel could be made with minimal damage to the remnant bundle and without interfering with the vision of the femoral footprint. 4 The current study confirmed the validity of the methods of creating the femoral tunnel viewed through the PL and TS portals. Many authors believe that improper femoral tunnel placement is a common reason for ACL reconstruction failure.…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Under visualization through the PL portal using a 70° arthroscope and through the TS portal, the anatomic femoral tunnel could be made with minimal damage to the remnant bundle and without interfering with the vision of the femoral footprint. 4 The current study confirmed the validity of the methods of creating the femoral tunnel viewed through the PL and TS portals. Many authors believe that improper femoral tunnel placement is a common reason for ACL reconstruction failure.…”
Section: Discussionsupporting
confidence: 78%
“…Between June 2011 and August 2014, 106 patients undergoing single-bundle, outside-in, remnant-preserving ACL reconstruction were recruited. 4 Patients were divided into 3 groups according to viewing technique (A group=36 patients; PL group=35 patients; TS group=35 patients). All patients agreed to be evaluated using 3-D CT within 1 week postoperatively.…”
Section: Demographicsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the basis of the fact that most mechanoreceptors exist in the subsynovial layer near the tibial attachment, many authors have introduced surgical techniques to save the remnant of the ruptured ACL. [1][2][3][4][5][6][7] However, most of these techniques are about preserving remnant, not covering the graft more with remnant.…”
mentioning
confidence: 99%